Inhibition of Fusarium Graminearum Growth and Deoxynivalenol Biosynthesis by Phenolic Compounds. Issue 43 (16th November 2022) - Ma, Yue; Zhou, Rui; Luo, Xiong‐Fei; Li, An‐Ping; Wang, Rui; Zhang, Bao‐Qi; Zhou, Han; Wu, Tian‐Lin; Wang, Yi‐Rong; An, Jun‐Xia; Zhang, Zhi‐Jun; Zhao, Wen‐Bin; et al.
Abstract: Phytopathogenic fungi infections have become a major threat to reduce crop yields and dampen human health globally. The mycelium growth inhibition method was adopted to evaluate the antifungal activity of commercially available natural and natural‐like phenols, bioassay results showed that most phenolic compounds exhibited excellent fungicidal activity against Fusarium graminearum, Rhizoctonia solani, Botrytis cinerea, Fusarium oxysporum f. sp . Vasinfectum, Sclerotinia sclerotiorum, and Magnaporthe oryzae . Particularly, compound Z‐5 exhibited an excellent inhibition rate of 100.00 % at 100 μg/mL and EC50 value of 3.20 μg/mL against Fusarium graminearum. In addition, compound Z‐5 displayed the best efficacy and superior fungicidal activity compared to azoxystrobin (EC50 =9.78 μg/mL) based on mycelial growth and spore germination. Significantly, compound Z‐5 at 200 μg/mL reduced 4‐deoxynivalenol production by over 98 % compared to the control, through down‐regulation of the gene expression of Tri5 and Tri6. Preliminary mechanism studies revealed that compound Z‐5 might exert its fungicidal activity by inducing accumulation of reactive oxygen species and lipid peroxidation, and causing cell membrane destruction and DNA synthesis interference. This study demonstrated the potent fungicidal activity of the natural‐like phenolic compound Z‐5 and highlighted its potential as an alternative agent to control F. graminearum . Abstract : Twenty‐one phenolic compounds such as thymol and carvacrol were selected as the research objects to screen the antifungal activities against 6 phytopathogenic fungi. The best antifungal compound Z‐5 and the most sensitive strain ( Fusarium graminearum ) were selected as further research objects. The mechanism was preliminarily discussed from the aspects of cell membrane destruction, oxidative stress, deoxynivalenol content, etc., which provided new ideas for the prevention and treatment of Fusarium graminearum .